An Implicit Scheme for Moving Walls and Multi-Material Interfaces in Weakly Compressible Materials (Communications in Computational Physics, 2020)
We propose a numerical method for the simulation of flows from weaklycompressible to low Mach regimes in domains with moving boundaries. Non-miscibleweakly compressible materials separated by an interface are included as well. Thescheme is fully implicit and it exploits the relaxation all-speed scheme introducedin [1]. We consider media with significantly different physical properties and constitutive laws, as fluids and hyperelastic solids. The proposed numerical scheme isfully Eulerian and it is the same for all materials. We present numerical validations bysimulating weakly compressible fluid/fluid, solid/solid and solid/fluid interactions.